Evaluation of Fundraising Mechanisms in the Zakat Collection Unit (UPZ) of the Ministry of Religious Affairs Office in Demak Regency) - Berlian, Ria; Savitri, Fania Mutiara (Ampera: A Research Journal on Politics and Islamic Civilization, 2023)
Zakat Collection Unit (UPZ) of the Ministry of Religious Affairs in Demak Regency is among the zakat management institutions certified by BAZNAS in Demak Regency, established in 2013. This study was conducted at the UPZ of the Ministry of Religious Affairsin Demak, focusing on the role of the zakat collector as the trustee responsible for managing funds. If the zakat collector fulfills their role effectively, it can lead to increased welfare for the other seven categories of zakat recipients. UPZ Ministry of Religious Affairs in Demak Regency relies solely on funds from muzakki as it lacks permanent donors. Fundraising activities aim to sustain social institutions or organizations by supporting their operational programs. Various fundraising methods are employed by institutions, each with its own strengths and weaknesses. The objectives of this research are twofold: (1) to analyze fundraising methods in the Zakat Collection Unit of the Ministry of Religion in Demak Regency, and (2) to evaluate the effectiveness of fundraising mechanisms in the same unit. The qualitative method was employed for this research, with data collected through triangulation techniques including interviews, observation, and documentation to ensure data validity. Data analysis followed the Miles and Huberman approach, involving data reduction, display, and drawing conclusions. Zakat Collection Unit (UPZ) of the Ministry of Religious Affairs in Demak Regency predominantly employs the indirect fundraising method for collecting zakat funds, avoiding direct contact with muzakki. However, with the advancement of digital technology, there is increasing potential for digital fundraising. UPZ Ministry of Religious Affairs Demak Regency conducts evaluations every semester during internal meetings, followed by the preparation of accountability reports for each program. These reports are then evaluated by advisors appointed by UPZ Ministry of Religious Affairs Demak, identifying program deficiencies and areas for improvement. Despite being conducted biannually, UPZ's evaluation approach encompasses input, process, and output, ensuring effective assessment of its activities and objectives